2022
DOI: 10.3389/fnbeh.2022.1011955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and retention interval on the retrieval and extinction of auditory fear conditioning

Abstract: Fear memory retrieval is relevant to psychiatric disorders such as post-traumatic stress disorder (PTSD). One of the hallmark symptoms of PTSD is the repeated retrieval and re-experiencing of the initial fear memory even long after the traumatic event has occurred. Women are nearly twice as likely to develop PTSD following a trauma than men, thus sex differences in the retrieval of fear memories is highly relevant for understanding the development and maintenance of PTSD. In the current study, we aimed to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, recent research has shown that darting is an unconditioned response (e.g., nonassociative; Trott et al, 2022). While we have previously failed to observe meaningful levels of darting in either male or female rats (Schoenberg et al, 2022), the current series of studies utilized different conditioning parameters than our previous work. Thus, the same video recordings used to score freezing were used to score instances of darting during each CS presentation during the renewal test sessions.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…However, recent research has shown that darting is an unconditioned response (e.g., nonassociative; Trott et al, 2022). While we have previously failed to observe meaningful levels of darting in either male or female rats (Schoenberg et al, 2022), the current series of studies utilized different conditioning parameters than our previous work. Thus, the same video recordings used to score freezing were used to score instances of darting during each CS presentation during the renewal test sessions.…”
Section: Methodsmentioning
confidence: 87%
“…Automated scoring of freezing was conducted as described by Schoenberg et al (2022). Video streams were acquired in near-infrared (720 P resolution, 29.97 frames per second) by Anpviz IPCameras (model IPC-B850W) mounted in each chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported sex differences in rodents in the fear memory task [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. For instance, in context fear conditioning, the freezing level of male rats was significantly higher than that of females, whether the stage was acquisition or extinction [ [42] , [43] , [44] , [45] ].…”
Section: Introductionmentioning
confidence: 99%
“…Pavlovian fear conditioning is a useful tool for studying the neurobiology of normal and pathological fear ( Johnson et al, 2012 ; LeDoux, 2014 ; Bowers and Ressler, 2015 ). Contextual fear conditioning is a paradigm capable of creating fear memory to context and retrieving of the conditioned fear memory is hypothesized to share common or similar mechanisms with the re-experiencing symptoms in post-traumatic stress disorder (PTSD) ( Bowers and Ressler, 2015 ; Chaaya et al, 2018 ; Schoenberg et al, 2022 ). Retrieval of the consolidated fear memory induces two opposing processes, reconsolidation and extinction.…”
Section: Introductionmentioning
confidence: 99%